Adsorption of Cadmium Metal in Liquid Waste Using Adsorbent Product of Pyrolysis of Teak Wood Biomass Waste - Putri Pratiwi Hamzah Aliah; Donvito Andrew Putra Sakke; Syarwan Hamid (Candela Edutech Indonesia, 2025)
Liquid waste containing cadmium metal has the potential to be dangerous if not handled properly. One effort to reduce the concentration of cadmium metal in liquid waste is by the adsorption method. Teak sawdust can be processed into charcoal using pyrolysis techniques. Furthermore, charcoal can be activated to be used as a bioadsorbent in liquid waste containing cadmium. The purpose of this study was to determine the mass ratio and optimum contact time of teak sawdust bioadsorbent in reducing the concentration of cadmium metal in liquid waste in the nickel industry. The study was conducted by pyrolyzing teak sawdust waste. The resulting charcoal was then activated. Furthermore, 50 mL of liquid waste containing cadmium was mixed with bioadsorbent and then adsorbed in time variations of 30, 60, 90, 120, 150, 180 minutes with the ratio of active mass to liquid analysis wastewater respectively 0.5g: 50mL, 1g: 50mL, 1.5g: 50mL, 2g: 50mL, and 2.5g: 50mL. After that, the Analysis wastewater was filtered with filter paper and the filtrate was analyzed for cadmium metal content using Atomic Absorption Spectrophotometry (AAS). The results showed that at a mass ratio of bioadsorbent and cadmium liquid waste of 200mg: 50 mL at 150 minutes, the value of the absorbed Cadmium metal content was 0.1845 mg/L or 98.8% of cadmium was absorbed on the bioadsorbent. Bioadsorbent from teak sawdust waste has the potential to be used to reduce the levels of Cadmium metal in liquid waste.